Ocena ranljivosti prsti in vegetacije - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Application of methodology for environmental vulnerability studies of two landscape- forming components, soils and natural vegetation, is presented. Evaluation of environmental vulnerability from the view of particular landscape-forming component can be adjusted to different spatial levels: smaller landscape-ecological units or larger, but still rather homogeneous landscape-ecological types. With sufficient data it is possible quite precisely to evaluate environmental vulnerability on the level of landscape units. On the level of landscape-ecological types the generalisation is much more significant. Despite this the environmental vulnerability studies give usoverview over the state of the environment and the impact of human pressures.
Keywords: ekološko ravnotežje; environmental protection; onesnaževanje okolja; onesnaževanje tal; pokrajinska ekologija; prst (pedologija); Slovenia; Slovenija; varstvo okolja; vegetacija